KOMPARASI CAPITAL ASSET PRICING MODEL VERSUS ARBITRAGE PRICING THEORY MODEL ATAS VOLATILITAS RETURN SAHAM - Mathius Tandiontong; Rusdin Rusdin (Jurnal Keuangan dan Perbankan, 2015)
Investing in the stock market is one option for investors. Investment in ordinary shares was classified as longterminvestments to be able to provide added value and the risk for fixed income. This study focused on thedifference of APTM versus CAPM, and it also focused on the sensitivity of the APTM on the stock returns. Thisstudy was based on the assumption that: there were differences in sectoral stock return volatility, volatility ofmarket risk factors, and macroeconomic risks affecting sectoral differences in the sensitivity of stock returns;there were differences in the results of testing the validity, robustness unconditional CAPM and APTMmultifactorial; and time-varying volatility referring to the phenomena of structural breaks and asymmetriceffect. The method of analysis used nested models with panel data. Data were analyzed by using secondary datafrom 2005-2012. The results of this study concluded that: there was no different sensitivity of stock returnsacross sectors, but there was different insensitivity between systematic risk factors, CAPM and APTM multifactorthat showed the inconsistency of the sectoral shares, but the proven model of unconditional CAPM wasvalid; the difference of factor risk premiums was as a result of the structural break, the financial crisis period of2008 within the period 2005-2012.